1977
DOI: 10.1172/jci108828
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of Surfactant Production by Oxytocin-Induced Labor in the Rabbit

Abstract: A B S T R A C T The respiratory distress syndrome is believed to be due to insufficient surfactant. It is known that there is a greater incidence of the respiratory distress syndrome among infants delivered by cesarean section before labor than among those delivered after labor at the same gestational age. The purpose of this study was to determine the effect of labor on the production of pulmonary surfactant.We measured the phospholipid content of lung lavage in newborn rabbits delivered by cesarean section b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

1977
1977
1998
1998

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(21 citation statements)
references
References 29 publications
0
21
0
Order By: Relevance
“…The developmental increase in the activity of this enzyme in rat lung cytosol parallels the increase in phospholipids in the same fraction (72 (68,133) and mouse (65) lung. There is a postnatal increase in the activity of CPT in the rabbit (70,71,81) while in the rat adult activities are considerably higher than those of the fetus or newborn (68,133). In two studies, however, the activity of lung CPT was reported to peak 1 to 2 days before term in the rat (67,135) and mouse (69).…”
Section: Enzymes Of Phospholipid Synthesismentioning
confidence: 93%
See 3 more Smart Citations
“…The developmental increase in the activity of this enzyme in rat lung cytosol parallels the increase in phospholipids in the same fraction (72 (68,133) and mouse (65) lung. There is a postnatal increase in the activity of CPT in the rabbit (70,71,81) while in the rat adult activities are considerably higher than those of the fetus or newborn (68,133). In two studies, however, the activity of lung CPT was reported to peak 1 to 2 days before term in the rat (67,135) and mouse (69).…”
Section: Enzymes Of Phospholipid Synthesismentioning
confidence: 93%
“…Birthandlaborhavebeenreported to stimulate surfactant production. There was a 2-to 4-fold increase in the phospholipid content of lung lavage from newborn rabbits delivered by cesarean section prior to labor at 29-31 days gestation (70,194). A similar finding was reported by Lawson et al.…”
Section: Other Factors Which Influence Surfactant Production In the Fmentioning
confidence: 98%
See 2 more Smart Citations
“…Studies with newborn rabbits have shown that the percent of acetone precipitable lecithin in pulmonary lavage (12), pulmonary stability (29), and pulmonary lavage phospholipid content (25) increase after birth. These findings indicate that immediately after birth the secretion of surfactant into the alveoli is increased over and above the fetal secretion rate.…”
Section: Speculationmentioning
confidence: 99%